(untitled) (International Journal of Studies in Nursing, 2022)
Background: Hospitalization has been a source of anxiety for young school-age patients. In addition to taking care of young patients’ physical problems, the primary caregivers will also encounter young patients’ emotional reactions. Understanding the anxiety status in young patients and primary caregivers to provide relevant measures is an important issue. Aim: To investigate the hospitalization anxiety levels in school-age children aged 6 to 12 years and primary caregivers, as well as their influencing factors. Subject and Methods: Cross-sectional research with a questionnaire survey was used as the methodology for the study. The enrollment period was between December 1, 2021, and August 31, 2022. For hospitalized young patients aged 6 to 12 years in the orthopedic ward of a medical center, after the consent was acquired at admission for 24 hours, the primary caregiver was assigned to complete the questionnaire. Result: The Post-Hospitalization Behavior Questionnaire (PHBQ) was used to investigate 39 young patients. The overall mean behavior scores was 51.5 ± 15.7 points, there were statistically significant differences for sex in general anxiety behavior scores, separation anxiety behavior scores, sleep anxiety behavior scores, apathy/withdrawal behavior scores, and total behavior scores, with higher post-hospitalization behavior scores in male young patients compared to that in females. In the Trait Anxiety Inventory for a family member, the mean score was 39 ± 12.6 points, with mild anxiety at 50%, moderate anxiety at 38.9%, and severe anxiety at 11.1%. Primary caregivers’ level of anxiety reached statistical significance in economic status, with an increased level of anxiety for those who were in lower economic positions (p=0.01). Conclusion: The PHBQ for young patients can be used as an assessment for their levels of anxiety, the levels of negative behaviors in boys are higher than that in girls. There were 50% of primary caregivers experienced moderate to severe anxiety, and the sources of anxiety were correlated with the economic status of the family. Recommendations: (1) Hospital anxiety in children is often overlooked and can be found by observing behavior. The PHBQ is an easy-to-use assessment tool and is recommended for routine use in hospitalized children to assess behavioral changes after pediatric surgery/hospitalization to help parents and medical staff evaluate children’s anxiety. (2) Hospitals can construct amusement equipment, and toys or arrange game activities to reduce the anxiety of hospitalization of school-age children.